Photocatalytic Tryptophan Alkylation for Chemoselective Peptide Modification - Lee, Joanna (2024)
A chemoselective peptide functionalisation strategy via photocatalytic tryptophan (Trp) modification has been developed. The versatility of the reaction is demonstrated by tethering a variety of difluoroalkyl groups to Trp using an organic photocatalyst and short irradiation times with visible light. Due to the mild and biocompatible reaction conditions, a range of complex peptides have been successfully functionalised to give a diverse library of small molecule-peptide conjugates. Results have confirmed site-selectivity for Trp in the presence of other amino acids, illustrating that this transformation can expand the field of chemoselective photo-bioconjugation. Applications of the methodology have been explored including protein modification and peptide stapling. For the latter, incorporation of the bromodifluorocarbonyl moiety into the peptide sequence during solid phase peptide synthesis (SPPS), enabled the synthesis of macrocyclic peptides.